Morphology of Parasitic and Free-living Adults of Rhabdias rubrovenosa (Nematoda, Rhabdiasidae) - Kuzmin, Yu.I. (Вестник зоологии, 2000)
The description of parasitic hermaphrodites, free-living males and females of Rhabdias rubrovenosa (Schneider, 1866) Semenov, 1929 is presented. Parasitic adults of the species are characterized by short vestibulum, absence of esophastome, pre-equatorial position of vulva and atrophy of rectum. The last two characters are less distinct in young individuals. Morphology of freeliving adults of the species is similar to that in corresponding stages of other species of the genus Rhabdias. Free-living females of R. rubrovenosa had not more than 2 eggs in the uteri; 1 or 2 larvae developed inside each female.